Relationship between motor abilities and executive functions in patients after pediatric stroke. Issue 4 (2nd October 2022) - Abgottspon, Stephanie; Steiner, Leonie; Slavova, Nedelina; Steinlin, Maja; Grunt, Sebastian; Everts, Regula
Abstract: Patients after pediatric stroke typically experience varying extent of motor and cognitive impairments. During rehabilitation, these impairments are often treated as separate entities. While there is a notion claiming that motor and cognitive functions are interrelated to some degree in healthy children, a minimal amount of evidence exists regarding this issue in patients after pediatric stroke. The purpose of this study was to investigate the association between motor abilities and executive functions in patients after pediatric arterial ischemic stroke. Twenty-seven patients (6 – 23 years) diagnosed with pediatric arterial ischemic stroke in the chronic phase (≥ 2 years after diagnosis, diagnosed < 16 years) and 49 healthy controls (6 – 26 years) were included in this study. Participants completed six tasks from standardized neuropsychological tests assessing the dimensions of executive functions, namely working memory, inhibition, and shifting. Additionally, we assessed hand strength and upper limb performance with two tasks each. In the patient group, the association between upper limb performance and executive functions was stronger than between hand strength and executive functions. Our results point toward the idea of a close interrelation between upper limb performance and executive functions. Training more complex and cognitively engaging motor abilities involving upper limb performance rather than basic motor abilities such as hand strength during a rehabilitation program may have the power to foster executive function development and vice versa in patients after stroke.